Contratos formais entre empresas processadoras de laranja e citricultores : um estudo de múltiplos casos entre os anos-safras de 1978/79 a 2011/12 na perspectiva dos citricultores - Carvalho, Murilo Secchieri de (Universidade Federal de São Carlos, 2015)
This thesis describes and analyzes from economic transaction cost (ETC) theoretical framework, formal agreements between ten citrus growers and a set of five citrus processors between 1978/79 to 2011/12 harvest seasons. The research uses an exploratory multiple-case study methodology, to deepen the historical relationships established, identifying transactional and relational elements involved, besides the maladaptation problems. The main objective is to verify empirically contractual governance form in São Paulo citrus complex, in the view of new institutional economics (NIE) and the contracts economy, deepening problems of contractual incompleteness, ex-ante and ex-post opportunism and external/internal transaction enforcements requirements. The result of this academic work is a relational contract model proposition that should be implemented in the negotiation between citrus processors and growers, a new orange box buy and sell contracts, supported by relational governance principles and arbitrated by an independent third party. This relational contract model could give greater governance stability and cohesion, reducing conflicts and also transaction cost between citrus growers and processors, modifying São Paulo citrus crises and stagnation that persist more than one decade.
Keywords: Governança; Citricultura; Contratos; Relacional; Governance; Citrus; Contract; Relational; ENGENHARIAS::ENGENHARIA DE PRODUCAO